2021
DOI: 10.1007/s00125-021-05380-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and hypoxia-inducible factors in diabetes and its complications

Abstract: Hypoxia-inducible factors (HIFs) are the key regulators of oxygen homeostasis in response to hypoxia. In diabetes, multiple tissues are hypoxic but adaptive responses to hypoxia are impaired due to insufficient activation of HIF signalling, which results from inhibition of HIF-1α stability and function due to hyperglycaemia and elevated fatty acid levels. In this review, we will summarise and discuss current findings about the regulation of HIF signalling in diabetes and the pathogenic roles of hypoxia and dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
144
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(176 citation statements)
references
References 54 publications
4
144
1
Order By: Relevance
“…The impact of low blood oxygen saturation on diabetes and its complications are still at a very early stage, but studies investigating the role of hypoxia in diabetes are emerging. 34 Some studies suggest that tissue hypoxia may be a central pathogenic factor in the development of diabetic kidney disease. [35][36][37] Indeed, renal hypoxia has been observed in type 2 diabetes with kidney disease, 38 and reduced renal cortical oxygenation has been found to predict a decline in renal function in persons with chronic kidney disease.…”
Section: Impactmentioning
confidence: 99%
“…The impact of low blood oxygen saturation on diabetes and its complications are still at a very early stage, but studies investigating the role of hypoxia in diabetes are emerging. 34 Some studies suggest that tissue hypoxia may be a central pathogenic factor in the development of diabetic kidney disease. [35][36][37] Indeed, renal hypoxia has been observed in type 2 diabetes with kidney disease, 38 and reduced renal cortical oxygenation has been found to predict a decline in renal function in persons with chronic kidney disease.…”
Section: Impactmentioning
confidence: 99%
“…Diabetic tissue damage leads to hypoxia. However, HIF-1 signaling is impaired in diabetes, which may contribute to the development of diabetic complications ( Catrina and Zheng, 2021 ). ARNT has been implicated in the development and progression of diabetes and is severely downregulated in the liver and pancreas of patients with diabetes ( Gunton et al, 2005 ; Pillai et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have suggested that disturbed hypoxic sensitivity may be responsible for impaired wound healing. [2][3][4][5][6][7] Cellular adaptive responses to hypoxia are mediated by the hypoxia-inducible factor (HIF). Stabilization of HIF-1α may be critical to improving wound healing.…”
Section: Introductionmentioning
confidence: 99%